Europe, globalization and sustainable development - Barry, John, 1966-; Baxter, Brian, 1949-; Dunphy, Richard (Routledge, 2004)
This edited volume considers the ways in which European states and the European Union can and should organize themselves economically and socially in order to address the challenges of sustainable development. It will interest students and researchers of environmental policy and European politics.
Keywords: Environmental policy -- Economic aspects -- Europe.; Anti-globalization movement -- Europe.; Environmental ethics -- Europe.; Globalization -- Social aspects.; Ecofeminism -- Europe.; Environmental protection -- Europe.; Environnement -- Politique gouvernementale -- Aspect économique -- Europe.; Altermondialisme -- Europe.; Éthique de l'environnement -- Europe.; Mondialisation -- Aspect social.; Écoféminisme -- Europe.; Environnement -- Protection -- Europe.; POLITICAL SCIENCE -- Public Policy -- Economic Policy.; BUSINESS & ECONOMICS -- Government & Business.; BUSINESS & ECONOMICS -- Development -- Economic Development.; BUSINESS & ECONOMICS -- Development -- Business Development.; BUSINESS & ECONOMICS -- Structural Adjustment.; BUSINESS & ECONOMICS -- Development -- General.; Anti-globalization movement; Ecofeminism; Environmental ethics; Environmental policy -- Economic aspects; Environmental protection; Globalization -- Social aspects; Europe